2016
DOI: 10.11130/jei.2016.31.2.275
|View full text |Cite
|
Sign up to set email alerts
|

Economic Integration in ASEAN+3 : A Network Analysis

Abstract: This paper analytically and graphically explores the characteristics of ASEAN+3's trade and Foreign Direct Investment integration over the 1990~2012 period by applying the tools of network analysis. Our results find evidence that the degree of trade and Foreign Direct Investment integration varies among ASEAN+3 member countries over the observation period. Second, ASEAN+3's intra-regional trade network seems to be more densely connected than its intra-regional Foreign Direct Investment network. Third, we revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
0
5
0
1
Order By: Relevance
“…A partir de la 2ª Reunión Informal de Kuala Lumpur, Malasia (1997), se incorporaron de manera informal China, Corea del Sur y Japón, hecho que se conoce como ANSEA más 3, y es desde entonces que estos tres países participan en todas las reuniones de la Asociación (Ramírez, 2001). La 11ª Cumbre de Kuala Lumpur fue el marco de ANSEA más 6, ya que además de los 10 miembros de la Asociación, más los 3 mencionados en el párrafo anterior, también se sumaron Australia, India y Nueva Zelanda (Nguyen, 2016).…”
Section: Anseaunclassified
“…A partir de la 2ª Reunión Informal de Kuala Lumpur, Malasia (1997), se incorporaron de manera informal China, Corea del Sur y Japón, hecho que se conoce como ANSEA más 3, y es desde entonces que estos tres países participan en todas las reuniones de la Asociación (Ramírez, 2001). La 11ª Cumbre de Kuala Lumpur fue el marco de ANSEA más 6, ya que además de los 10 miembros de la Asociación, más los 3 mencionados en el párrafo anterior, también se sumaron Australia, India y Nueva Zelanda (Nguyen, 2016).…”
Section: Anseaunclassified
“…Despite abundant literature in this area of research, specific research is needed with lower criteria and stringency to tolerate the differences between nominal levels of each economy with deviations that remains stochastic in nature. This study fills the need to evaluate the integration of all ASEAN members, whereas the previous related studies were limited to a part of ASEAN or other regions (see for example Tang, 2012;Candelon & Gil-Alana, 2006;), were limited to either financial or real sector aspect of the integration (see for example Nguyen et al 2016;Zhang & Matthews, 2019), or examining a specific event (Rahman & Shahari, 2019). More importantly, this study is the first on this topic that investigates the impact of the establishment of the AEC on the pace and direction of ASEAN economic integration.…”
Section: Introductionmentioning
confidence: 99%
“…For instance , Basnet et al (2015) are interested in assessing the monetary policy synchronization among the founding members of the ASEAN and found that the real exchange rates of Malaysia, Philippines, Singapore, and Thailand share common cycles in the short term and have common trends in the long term, but the Indonesian currency does not share these relationships. Sethapramote 1) See Nguyen et al (2016) for discussions on trade and foreign direct investment integration in ASEAN.…”
Section: Introductionmentioning
confidence: 99%